2011
DOI: 10.1111/j.1399-3062.2011.00638.x
|View full text |Cite
|
Sign up to set email alerts
|

Disseminated Burkholderia gladioli infection in a lung transplant recipient with underlying hypocomplementemic urticarial vasculitis

Abstract: Burkholderia gladioli is difficult to definitively identify within the laboratory using phenotypic testing alone. We describe a case of recurrent B. gladioli infection in a lung transplant recipient with underlying hypocomplementemic urticarial vasculitis syndrome, discuss the difficulties encountered with laboratory identification, provide a review of the methodology required for definitive identification, and discuss potential pathophysiologic mechanisms in this patient responsible for the difficulty in trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
(21 reference statements)
1
2
0
Order By: Relevance
“… 4 One case report showed that a reduction of immunosuppression combined with antimicrobials led to clearance of B gladioli infection but ultimately led to the patient's death from an invasive fungal infection of the lungs. 20 Infection with this bacterium is often associated with a poor prognosis, as with our patient. 20 …”
Section: Discussionsupporting
confidence: 52%
“… 4 One case report showed that a reduction of immunosuppression combined with antimicrobials led to clearance of B gladioli infection but ultimately led to the patient's death from an invasive fungal infection of the lungs. 20 Infection with this bacterium is often associated with a poor prognosis, as with our patient. 20 …”
Section: Discussionsupporting
confidence: 52%
“…50 Despite the growing prevalence of automated microbial identification instruments, there are still ongoing problems with accurate identification of members of the Burkholderia family in clinical settings that have been outlined in several studies regarding B. gladioli. 51,52 It is crucial that clear differentiation of species is achieved, due to the range of outcomes attributable to each different member of this complex of organisms.…”
Section: Ishlt Candidate Selection Consensus Guidelinesmentioning
confidence: 99%
“…Despite resolution of B. gladioli infection, the patient ultimately succumbed to a fatal pulmonary Aspergillus infection. 52 These cases suggest that extended, strong antibiotic use may alter the underlying bacterial composition of the lung, in an attempt to treat B. gladioli infection, and thus leave patients susceptible to pulmonary infection with fungal and viral species. Further studies to determine the mechanisms underlying this phenomenon should prove useful in guiding future treatment decision-making.…”
Section: Ishlt Candidate Selection Consensus Guidelinesmentioning
confidence: 99%